ANALISIS KELUHAN PELANGGAN TERHADAP DISTRIBUSI MINYAK PELUMAS DI MANADO - Yohanes Vendmard; Agung Sutrisno; Johan S C Neyland (JURNAL POROS TEKNIK MESIN UNSRAT, 2016)
The need of lubricant based on the huge number of users and the significant increase of costumer each year has made lubricant as one of profitable mechanical thing. Quality control has a very important role in maintaining customerâ€™s satisfaction as well. This research aims to analyze the service quality, mainly in distribution process, based on customerâ€™s complaint. Customers were asked to give score on some attributes and fill in a questionnaire about their experience related to various types of complaints. Data taken were then analyzed using AHP method. The results show that â€œAssuranceâ€ has the highest weight score (0.313) and â€œTangibleâ€ has the lowest score (0.118). The multiplication of weight score and faction resulting â€œReliableâ€ as the most critical attribute regarding service quality (0.9583)â€”close to â€œUnderstandingâ€ (0.09567). Keywords: Quality control, customerâ€™s complaint, distribution, lubricant, Analysis Hierarchy Process (AHP)